2020
DOI: 10.3390/biom10040583
|View full text |Cite
|
Sign up to set email alerts
|

uL3 Mediated Nucleolar Stress Pathway as a New Mechanism of Action of Antiproliferative G-quadruplex TBA Derivatives in Colon Cancer Cells

Abstract: The antiproliferative G-quadruplex aptamers are a promising and challenging subject in the framework of the anticancer therapeutic oligonucleotides research field. Although several antiproliferative G-quadruplex aptamers have been identified and proven to be effective on different cancer cell lines, their mechanism of action is still unexplored. We have recently described the antiproliferative activity of a heterochiral thrombin binding aptamer (TBA) derivative, namely, LQ1. Here, we investigate the molecular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 48 publications
0
19
0
Order By: Relevance
“…HCT 116 p53−/− cells and uL3ΔHCT 116 p53−/− cells were seeded into 35 mm tissue culture plates at a confluency about 50–60%. Then, cells were starved overnight and treated with 500 µM AdoMet for 72 h. After treatment, the cells were harvested and centrifuged at 400× g for 5 min, washed once with cold PBS and stained in a PI solution as previously reported [ 53 ]. Flow cytometric analysis was performed using a BD Accuri™ C6 flow cytometer (BD Biosciences).…”
Section: Methodsmentioning
confidence: 99%
“…HCT 116 p53−/− cells and uL3ΔHCT 116 p53−/− cells were seeded into 35 mm tissue culture plates at a confluency about 50–60%. Then, cells were starved overnight and treated with 500 µM AdoMet for 72 h. After treatment, the cells were harvested and centrifuged at 400× g for 5 min, washed once with cold PBS and stained in a PI solution as previously reported [ 53 ]. Flow cytometric analysis was performed using a BD Accuri™ C6 flow cytometer (BD Biosciences).…”
Section: Methodsmentioning
confidence: 99%
“…The whole of the data strongly suggest that the cytotoxic activity contributing to the antiproliferative properties of these ODNs, being completely devoid of anticoagulant activity (see above), should not involve neither the thrombin-mediated processes associated to cancer ( 35 , 36 ), neither the described pathway related to the guanine-based products derived from the degradation of G-rich ODNs ( 33 ), since they are highly resistant to nucleases (see below). It is important to note, that these ODNs are structurally correlated to heterochiral LQ1, previously studied by our group, whose potent cytotoxic activity toward the HCT 116 p53−/− cells is mediated by a perturbation of nucleolar function with consequent activation of a nucleolar stress response pathway p53 independent and uL3 dependent ( 21 ). Further research is needed to verify whether the cytotoxic activity of the investigated ODNs is mediated by the activation of the same molecular pathway.…”
Section: Resultsmentioning
confidence: 96%
“…Recently, we have shown that the homochiral L-TBA and the heterochiral LQ1, formerly TBA-D13 (the last mostly composed by l -residues except for the thymidines in the small TT loops), are endowed with noteworthy antiproliferative activities against Calu-6 and HCT 116 p53−/− cells, an outstanding stability to nucleases but no anticoagulant activity ( 20 ). In a following study, we investigated the molecular mechanisms of LQ1 activity and the structural and antiproliferative properties of two further heterochiral TBA derivatives (differing from LQ1 only by the small loop base-compositions), thus highlighting the critical importance of the small loops for the antiproliferative activity against Calu-6 and HCT 116 p53−/− cells ( 21 ).…”
Section: Introductionmentioning
confidence: 99%
“…We have previously demonstrated that uL3 is a key mediator of nucleolar stress induced by several chemotherapeutic drugs, including 5-fluorouracil (5-FU) [ 34 , 35 , 36 ], Oxaliplatinum (OHP) [ 37 , 38 ], Actinomycin D (Act D) [ 39 , 40 ] and Niclosamide, in p53-mutated lung and p53-deleted colon cancer cells [ 41 , 42 ]. Specifically, we identified a new nucleolar stress pathway activated upon cell treatment with chemotherapeutic drugs that is p53-independent and uL3-dependent [ 22 , 43 , 44 ]. Transcriptome analysis of genes and pathways that are differentially expressed in colon cancer cells devoid of p53, in the presence or in absence of uL3, and in condition of nucleolar stress activated by Act D, revealed that uL3 deficient colon cancer cells showed the upregulation of pathways related to autophagy activation.…”
Section: Nucleolar Stressmentioning
confidence: 99%